2018
DOI: 10.1371/journal.pone.0207475
|View full text |Cite
|
Sign up to set email alerts
|

Diversity across major and candidate genes in European local pig breeds

Abstract: The aim of this work was to analyse the distribution of causal and candidate mutations associated to relevant productive traits in twenty local European pig breeds. Also, the potential of the SNP panel employed for elucidating the genetic structure and relationships among breeds was evaluated. Most relevant genes and mutations associated with pig morphological, productive, meat quality, reproductive and disease resistance traits were prioritized and analyzed in a maximum of 47 blood samples from each of the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
103
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(118 citation statements)
references
References 105 publications
10
103
4
1
Order By: Relevance
“…An intronic mutation in IGF2 (g.3072G > A) is strongly related to fat depot and muscle development when the G allele is present [81]. In AL pigs the G allele is fixed while in BI the A allele is residual (0.01) [6]. IGF2 was found significantly overexpressed in BI (log2 FC = −0.884, p < 0.05) despite their leaner phenotype which indicates that fat deposition is regulated at other levels.…”
Section: Gene Expression Analysis: Deseq2mentioning
confidence: 97%
See 4 more Smart Citations
“…An intronic mutation in IGF2 (g.3072G > A) is strongly related to fat depot and muscle development when the G allele is present [81]. In AL pigs the G allele is fixed while in BI the A allele is residual (0.01) [6]. IGF2 was found significantly overexpressed in BI (log2 FC = −0.884, p < 0.05) despite their leaner phenotype which indicates that fat deposition is regulated at other levels.…”
Section: Gene Expression Analysis: Deseq2mentioning
confidence: 97%
“…In pigs, taste perception can influence feeding patterns which can consequently determine production traits and TAS2R39 in particular has been previously associated with increased lipid deposition [54]. A recent study that investigated the allele frequency of known polymorphisms with associated meat quality traits in European local pig breeds [6], including AL and BI, found that the missense mutation p.Leu37Ser in TAS2R39 associated with higher backfat deposition is practically absent in AL (0.01), while in BI is present in 13% of individuals. This contradicts phenotypic data and suggests that regulation of lipid content may occur at different levels and differ in pathways from AL pigs.…”
Section: Gene Expression Analysis: Deseq2mentioning
confidence: 99%
See 3 more Smart Citations